2023
DOI: 10.3389/fmicb.2023.1106340
|View full text |Cite
|
Sign up to set email alerts
|

ArcR contributes to tolerance to fluoroquinolone antibiotics by regulating katA in Staphylococcus aureus

Abstract: Staphylococcus aureus is an opportunistic pathogen that shows a unique ability to quickly respond to a variety of antibiotics. The Crp/Fnr family transcriptional regulator ArcR controls expression of arginine deiminase pathway genes arcABDC, which enable the utilization of arginine as an energy source for cell growth under anaerobic conditions. However, ArcR shares low overall similarity with other Crp/Fnr family proteins, suggesting that they differ in the response to environmental stress. In this study, MIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The immunity evasion of S. aureus by opportunistic infections is a key characteristic closely associated with bacterial virulence and immune-modulating factors [ 13 ]. In particular, the catalase A gene ( katA ) of S. aureus modulates antibiotic resistance and oxidative stress [ 14 ]. Thus, S. aureus can easily adapt to other aerobic environments during infections owing to the high H 2 O 2 resistance of the katA gene [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunity evasion of S. aureus by opportunistic infections is a key characteristic closely associated with bacterial virulence and immune-modulating factors [ 13 ]. In particular, the catalase A gene ( katA ) of S. aureus modulates antibiotic resistance and oxidative stress [ 14 ]. Thus, S. aureus can easily adapt to other aerobic environments during infections owing to the high H 2 O 2 resistance of the katA gene [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…ArcR affected the utilization of arginine under anaerobic conditions through the regulation of the pathway genes arcABDC [ 32 ]. Our previous study showed that ArcR contributed to the tolerance of fluoroquinolone antibiotics in S. aureus [ 33 ]. In this study, we showed the function of ArcR in virulence and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%